2017
DOI: 10.1177/0046958016685836
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Cloud Computing Success Model for Hospitals in Taiwan

Abstract: The purpose of this study is to understand the critical quality-related factors that affect cloud computing success of hospitals in Taiwan. In this study, private cloud computing is the major research target. The chief information officers participated in a questionnaire survey. The results indicate that the integration of trust into the information systems success model will have acceptable explanatory power to understand cloud computing success in the hospital. Moreover, information quality and system qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…However, in addition to policy processes, there are hospital-level factors that play a critical role in this transition [ 161 ]. While hospitals that receive adequate funding and technical support are more adept at cloud adoption, it has generally been observed that inter-hospital and intra-hospital factors are more complex [ 77 ] and can vary from one country to the other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in addition to policy processes, there are hospital-level factors that play a critical role in this transition [ 161 ]. While hospitals that receive adequate funding and technical support are more adept at cloud adoption, it has generally been observed that inter-hospital and intra-hospital factors are more complex [ 77 ] and can vary from one country to the other.…”
Section: Discussionmentioning
confidence: 99%
“…A key reason for this is that enhanced cybersecurity entails financial and opportunity costs. Institutions find it difficult to allocate adequate resources for the purpose within their limited resources [ 161 ]. This is a significant barrier for cloud adoption as any potential threat may deter ongoing policy efforts if not handled well [ 125 ].…”
Section: Barriers To Cloud Adoption In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…CC is also elastic in that it can expand and contract depending on the system use by the client and thus, it assists in resolving feasibility and scalability challenges [23]. Throughout the previous years, Jordanian hospitals have begun to adopt CC for IT services platform, but prior studies only focused on the critical factors affecting the decisions to adopt among users [24,25], with only few carried out to shed light on CC success within hospitals [26,27]. Particularly, Garrison et al [25] stressed on the critical role of the 3 IT capabilities, namely managerial, technical, and relational, towards CC success, albeit their study was limited to IT capabilities.…”
Section: Cloud Computing In Hismentioning
confidence: 99%
“…These aspects are subject to ongoing discussions and debates in the EOSC initiative [35]; for instance, progress has been made in the Human Brain Project (HBP) through its Ethics and Society sub-project in collaboration with the project platforms [36,37]. Other examples of data sharing that are compliant with data protection policies can be found in the recent literature [38][39][40][41][42][43][44][45]. Furthermore, there is the issue of capacity, with the amount of data starting to strain the infrastructure of any individual hospital or research institute.…”
Section: Existing Ethics and Legal Frameworkmentioning
confidence: 99%